Delayed Metastasis of Clear Cell Sarcoma of Kidney to Bladder After 7 Disease-Free Years. (4th March 2018) - Lang, Adam; Dehner, Louis P.
ABSTRACT: Introduction : Clear cell sarcoma of the kidney (CCSK) is childhood neoplasm with its own distinctive pattern of metastasis and may appear after a disease free interval of 5 years or more. Materials and Methods : Histopathology and immunohistochemistry were available from the radical nephrectomy and the later partial cystectomy, which was performed after a seven disease-free interval. Results : The pathologic features of the primary tumor were those of a classic CCSK with a monotypic pattern of uniform rounded to ovoid tumor cells with a background network of delicate blood vessels. By contrast, the bladder recurrence had a myxoid hypocellular appearance (one of the known variant patterns of CCSK). Both tumors displayed immunopositivity for Cyclin-D1 and CD117 with a less intense reaction in the bladder metastasis. Conclusions : This case demonstrates that CCSK has the potential to metastasize after a prolonged disease-free interval and may have deceptively bland histopathologic features.